Effects of some dietary crude plant extracts on the growth and gonadal maturity of Nile tilapia (Oreochromis niloticus) and their resistance to Streptococcus agalactiae infection - Kareem, Zana H.; Abdelhadi, Yasser M.; Christianus, Annie; Abd Karim, Murni Marlina; Romano, Nicholas Paul (Springer, 2016)
A 90-day feeding trial was conducted on the growth performance, feeding efficacy, body indices, various hematological and plasma biochemical parameters, and histopathological examination of the gonads from male and female Nile tilapia fingerlings when fed different crude plant extracts from Cinnamomum camphora, Euphorbia hirta, Azadirachta indica, or Carica papaya at 2 g kg−1 compared to a control diet. This was followed by a 14-day challenge to Streptococcus agalactiae. All treatments were triplicated, and each treatment consisted of 30 fish. Results showed that C. papaya extracts were the most effective at delaying gonadal maturation to both male and female tilapia, as well as significantly increasing (P < 0.05) growth performance compared to the control treatment. Similarly, dietary C. camphora and E. hirta extracts also significantly improved growth, while no significant growth effect was detected between the A. indica and control treatments (P > 0.05). Further, crude body lipid was lower in the C. camphora, E. hirta and C. papaya treatments, but was only significantly lower for the E. hirta treatment compared to the control. Meanwhile, none of the hematological or biochemical parameters were significantly affected, although plasma ALT was significantly lower for tilapia fed A. indica compared to the control. After the 14-day bacterial challenge, tilapia fed C. camphora supplementation had significantly higher survival, compared to the control, but was not significantly higher than the other supplemented diets. Results indicate that dietary C. papaya extract can significantly promote growth and delay gonadal maturation to both male and female tilapia, while C. camphora was the most effective prophylactic to S. agalactiae and may be a cost-effective and eco-friendly alternative to antibiotics.